Prey Capture, Ingestion, and Digestion Dynamics of Octopus vulgaris Paralarvae Fed Live Zooplankton - Nande, Manuel; Presa, Pablo; Roura, Álvaro; Andrews, Paul L. R.; Pérez, Montse (Frontiers in Physiology, 2017)
Octopus vulgaris is a species of great interest in research areas such as neurobiology, ethology and ecology but is also a candidate species for aquaculture as food resource as well as source to alleviating the fishing pressure on its wild populations. This study aimed to characterize the predatory behaviour of O. vulgaris paralarvae and to quantify their digestive activity. Those processes were affordable using the video-recording analysis of 3 dph, mantle-transparent paralarvae feeding on 18 types of live zooplanktonic prey. We show that octopus paralavae attack, immobilize, drill and ingest live cladocerans and copepods with 100% efficiency, which decreases dramatically to 60% on decapod prey (Pisidia longicornis). The majority (85%) of successful attacks targeted the prey cephalothorax while unsuccessful attacks either targeted the dorsal cephalothorax or involved prey defensive strategies (e.g. juvenile crab megalopa) or prey protected by thick carapaces (e.g. Gammaridae). After immobilization, the beak, the buccal mass and the radula were involved in exoskeleton penetration and content ingestion. Ingestion time of prey content was rapid for copepods and cladocerans (73.13 ± 23.34 s) but much slower for decapod zoeae and euphasiids (152.49 ± 29.40 s). Total contact time with prey was always <5min. Contrary to the conventional view of crop filling dynamics observed in adult Octopus vulgaris, food accumulated first in the stomach of paralarvae and the crop filled after the stomach volume plateaued. Peristaltic crop contractions (~18/min) moved food into the stomach (contractions ~30/min) from where it passed to the caecum. Pigmented food tracers were seen to enter the digestive gland, 312 ± 32 s after the crop reached its maximum volume. Digestive tract contents passed into the terminal intestine by peristalsis (contraction frequency ~50/min) and defaecation was accompanied by an increased frequency of mantle contractions. Current results provide novel insights into both, O. vulgaris paralarvae – live prey capture strategies and the physiological mechanisms following ingestion, a key information to develop an effective rearing protocol for O. vulgaris.